British Cycling unveils wild track bike for 2020 Tokyo Olympics - Huang, J. (CyclingTips, 2019)
The British Cycling Federation has concocted a number of unusual machines for its track racers over the years, and the 2020 Olympic Games in Tokyo, Japan, will clearly be no different. With aerodynamic input from Lotus Engineering and manufacturing by Hope Technology, British Cycling`s latest track bike is arguably its wildest yet.